2022
DOI: 10.1155/2022/8417784
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Innovation Mechanism Based on Linkages between Core Knowledge and Periphery Knowledge: The Case of R&D Cooperation between Latecomers and Forerunners

Abstract: With rapid changes in technology, knowledge innovation has become more and more complex. Complex partners facilitate knowledge creation and innovation in complex problem-solving. Relying on R&D cooperation with forerunners, latecomers can acquire new knowledge factors and new ideas and use them to create new knowledge. This study demonstrated the knowledge innovation mechanism based on linkages between periphery knowledge and core knowledge with knowledge map theory and set methodology. A case of R&D c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…With the rise of the global knowledge economy, innovation has become a crucial component for organizations to get a competitive edge and demonstrate exceptional performance (Li et al, 2022), and the implementation and utilization of KM are too (Hassan & Raziq, 2019). Previous studies have identified a positive relationship between KM and innovation (Du Plessis, 2007;Gardeazabal et al, 2023;Honarpour et al, 2018;Mardani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With the rise of the global knowledge economy, innovation has become a crucial component for organizations to get a competitive edge and demonstrate exceptional performance (Li et al, 2022), and the implementation and utilization of KM are too (Hassan & Raziq, 2019). Previous studies have identified a positive relationship between KM and innovation (Du Plessis, 2007;Gardeazabal et al, 2023;Honarpour et al, 2018;Mardani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%